1981
DOI: 10.1161/01.cir.63.6.1285
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin sensitivity in amyloid cardiomyopathy.

Abstract: Digoxin (5 mg/ml) was added to 10-mg and 20-mg pellets of purified primary and secondary amyloid fibrils, a normal human liver and heart homogenate and a homogenate from the heart of a patient with amyloid cardiomyopathy who had not received digitalis. After centrifugation, the supernatants were recovered and assayed for digoxin concentrations. Aliquots from the sediments were studied for the presence of digoxin, using rabbits antidigoxin antiserum and an indirect immunofluorescent technique. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
10

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(114 citation statements)
references
References 16 publications
0
102
0
10
Order By: Relevance
“…74 As a result of the binding to myocardial amyloid, cardiac digoxin levels may be elevated, and digoxin toxicity can exist even in the setting of "therapeutic" serum digoxin levels. Nevertheless, when atrial fibrillation with a rapid ventricular response is present, digoxin (administered cautiously) can be usually safely and successfully used.…”
Section: Cardiac Amyloidosis 2053mentioning
confidence: 99%
“…74 As a result of the binding to myocardial amyloid, cardiac digoxin levels may be elevated, and digoxin toxicity can exist even in the setting of "therapeutic" serum digoxin levels. Nevertheless, when atrial fibrillation with a rapid ventricular response is present, digoxin (administered cautiously) can be usually safely and successfully used.…”
Section: Cardiac Amyloidosis 2053mentioning
confidence: 99%
“…Echocardiographic tracking over the 5 years of follow-up showed thickening of the RV wall, decreased RV wall motion and an increase in the size of RV chamber, which are all consistent with predominantly right-sided heart failure in patients with cardiac amyloidosis. 15 Patients with cardiac amyloidosis can become sensitized to digoxin, 10 which binds to amyloid fibrils, 16 and despite very cautious administration, this occurred in the present patient. ACEI and -blockers failed to control the heart failure because of further weakness and hypotension.…”
Section: Discussionmentioning
confidence: 62%
“…7 However, the propensity of digoxin to bind with amyloid protein fibrils increases its availability and causes digoxin toxicity, even at therapeutic digoxin levels. 49 Pacemakers have been used in patients with symptomatic bradycardia. The atrial and ventricular pacing thresholds have been shown to be higher in these patients.…”
Section: Discussionmentioning
confidence: 99%